2008
DOI: 10.1074/jbc.m708829200
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Requirement of the Epithelial Sodium Channel for Maintenance of Epidermal Barrier Function

Abstract: In skin, the physiological consequence of an epithelial sodium channel (ENaC) deficiency is not obvious directly at birth. Nevertheless, within hours after birth, mice deficient for the ␣-subunit of the highly amiloride-sensitive epithelial sodium channel (␣ENaC/Scnn1a) suffer from a significant increased dehydration. This is characterized by a loss of body weight (by 6% in 6 h) and an increased transepidermal water loss, which is accompanied by a higher skin surface pH in 1-day-old pups. Although early and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…7,9 ␣ENaC deficiency also induces death shortly after birth, with a lung, skin, and kidney phenotype. 8,18 Mice in which ␣ENaC is deleted specifically in the CD are viable and do not show disturbances in sodium and potassium balance even when subjected to challenging diets. 10 This suggested that the CNT is important in controlling ENaC-mediated sodium reabsorption in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 ␣ENaC deficiency also induces death shortly after birth, with a lung, skin, and kidney phenotype. 8,18 Mice in which ␣ENaC is deleted specifically in the CD are viable and do not show disturbances in sodium and potassium balance even when subjected to challenging diets. 10 This suggested that the CNT is important in controlling ENaC-mediated sodium reabsorption in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose that ENaC-mediated sensing of the EF plays a fundamental physiologic role in directing cell migration and contributing to wound repair. Additionally this work describes a novel role for ENaC in the epidermis, beyond the previously described function of modulating epidermal barrier formation (Charles et al, 2008).…”
Section: Enac Protein Mediates Galvanotaxismentioning
confidence: 99%
“…Although the genetic ablation of the aENaC gene in mice results in a postnatal lethal phenotype due to an inability to clear lung fluids (Hummler et al, 1996), the role of this channel in skin epithelial biology is not yet elucidated. aENaC knockout mice do have abnormal lipid composition in their stratum corneum (Mauro et al, 2002;Charles et al, 2008), but these animals do not survive long enough to perform in vivo skin investigations. In humans, loss-offunction mutations of aENaC genes cause a rare autosomal, recessive disease: pseudohypoaldosteronism type 1 (Chang et al, 1996;Strautnieks et al, 1996), resulting in salt loss, hyperkalemia and metabolic acidosis in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…In these epithelia ENaC is the rate-limiting step for sodium absorption and plays a critical role in the maintenance of body sodium balance (1)(2)(3)(4). In addition, ENaC expression has been reported in a number of other tissues, including skin, endothelial cells, vascular smooth muscle cells, and neurons where its physiological role remains to be determined (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%